Eccentric Exercise Reduces Upper Trapezius Muscle Stiffness Assessed by Shear Wave Elastography and Myotonometry - Kisilewicz, Aleksandra; Madeleine, Pascal; Ignasiak, Zofia; Ciszek, Bogdan; Kawczynski, Adam; Larsen, Ryan Godsk (Frontiers in Bioengineering and Biotechnology, 2020)
In this study, we tested the hypotheses that unaccustomed eccentric exercise (ECC) would change the elastic modulus and dynamic stiffness of the upper trapezius (UT) muscle and that these changes would correlate with increases in muscle thickness, reflecting muscle edema. Shear wave elastography was used to measure elastic modulus, dynamic stiffness was assessed using myotonometry, and muscle thickness was measured using ultrasonography. All measurements were performed at four locations over the UT before and 24 h after a single bout of ECC. Fourteen healthy participants (23.2 ± 3.0 years) took part in the study. Overall, ECC resulted in decreased elastic modulus (from 45.8 ± 1.6 to 39.4 ± 1.2 kPa, p < 0.01) and dynamic muscle stiffness (from 369.0 ± 7.3 to 302.6 ± 6.0 N/m, p < 0.001). Additionally, ECC resulted in increased muscle thickness (from 6.9 ± 0.4 to 7.3 ± 0.4 mm, p < 0.001). Spatial changes (across the four locations) were found for elastic modulus, stiffness and thickness. No significant correlations were found between changes in measures of muscle stiffness, or between changes in stiffness and changes in thickness. In conclusion, the present study showed that ECC altered biomechanical muscle properties, reflected by decreased elastic modulus and dynamic muscle stiffness 24 h after ECC.